Exosomes in Intestinal Inflammation - Ayyar, Kanchana K.; Moss, Alan C. (Frontiers in Pharmacology, 2021)
Exosomes are 30–150 nm sized vesicles released by a variety of cells, and are found in most physiological compartments (feces, blood, urine, saliva, breast milk). They can contain different cargo, including nucleic acids, proteins and lipids. In Inflammatory Bowel Disease (IBD), a distinct exosome profile can be detected in blood and fecal samples. In addition, circulating exosomes can carry targets on their surface for monoclonal antibodies used as IBD therapy. This review aims to understand the exosome profile in humans and other mammals, the cargo contained in them, the effect of exosomes on the gut, and the application of exosomes in IBD therapy.